Leading standards and the business cycle: Evidence from loan survey releases - Lucas Hafemann; Peter Tillmann (Philipps-University Marburg, School of Business and Economics, 2021)
The Fed's Senior Loan Officer Opinion Survey (SLOOS) is widely considered a good indicator of banks' lending conditions. We use the change in corporate bond spreads on SLOOS release days to instrument changes in lending standards. A series of estimated IV local projections shows that lending standards have highly significant effects on macroeconomic and financial variables. A relaxation of standards expands economic activity and eases financial conditions. We then use the change in spreads and the change in the VIX index on release days to identify a pure credit supply shock and a risk-taking shock using sign restrictions in a Bayesian VAR model. We find that an easing in lending has different consequences for both types of shocks. While the VIX, the excess bond premium and stock prices decrease after a pure credit supply shock, they increase after a risk-taking shock.
Keywords: E32; E44; G14; 330; loan survey; credit supply; risk-taking; instrumental variable local projections; shock identification